2013
DOI: 10.1186/1472-6882-13-302
|View full text |Cite
|
Sign up to set email alerts
|

Total nasal resistance among Sasang constitutional types: a population-based study in Korea

Abstract: BackgroundThere have been many attempts to find an objective phenotype by Sasang constitutional types (SCTs) on an anatomical, physiological, and psychological basis, but there has been no research on total nasal resistance (TNR) among SCTs.MethodsWe assessed the value of the TNR in the SCTs classified by an integrated diagnostic model. Included in the study were 1,346 individuals (701 males, 645 females) who participated in the Korean Genome and Epidemiology Study (KoGES). The TNR was measured by active anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…height, weight, waist circumference, blood pressure, blood count, biochemical analysis, including blood sugar, lipid profiles and other biomarkers to evaluate current health status; Table 4 ). In addition to the core variables, the KoGES has also been promoting various ancillary and collaborative measurements and studies, including oral glucose tolerance test, carotid intima-media thickness test, pulse wave velocity (PWV) test, electrocardiography, pulmonary function test, bone mineral density, brain magnetic resonance imaging, osteoporosis, periodontal diseases and oriental medicine study, 7 , 8 that lead to numerous in-depth research outcomes. A list of these special clinical tests is shown in Supplementary Table 4 (available as Supplementary data at IJE online).…”
Section: What Has Been Measured?mentioning
confidence: 99%
“…height, weight, waist circumference, blood pressure, blood count, biochemical analysis, including blood sugar, lipid profiles and other biomarkers to evaluate current health status; Table 4 ). In addition to the core variables, the KoGES has also been promoting various ancillary and collaborative measurements and studies, including oral glucose tolerance test, carotid intima-media thickness test, pulse wave velocity (PWV) test, electrocardiography, pulmonary function test, bone mineral density, brain magnetic resonance imaging, osteoporosis, periodontal diseases and oriental medicine study, 7 , 8 that lead to numerous in-depth research outcomes. A list of these special clinical tests is shown in Supplementary Table 4 (available as Supplementary data at IJE online).…”
Section: What Has Been Measured?mentioning
confidence: 99%
“…Lee showed that the TE constitution is an independent risk factor for obstructive sleep apnea (Lee et al, 2013a). Yoon evaluated the total nasal resistance for the Sasang constitution in young males, as well as six syndromes in patients with functional dyspepsia compared with healthy subjects; the study found that SE constitution is primarily related to functional dyspepsia (Yoon et al, 2013). Ahn performed an association study to compare subclinical hypothyroidism and the Sasang constitutions (Ahn et al, 2012).…”
Section: Somatotype Characteristicsmentioning
confidence: 98%